What a difference a bay makes: natural variation in dietary resources mediates growth in a recently settled herbivorous fish - Priest, M.; Halford, A.; Clements, K.; Douglas, E.; Abellana, S.; McIlwain, Jennifer (Springer Verlag, 2016)
Processes acting during the early stages of coral reef fish life cycles have a disproportionate influence on their adult abundance and community structure. Higher growth rates, for example, confer a major fitness advantage in larval and juvenile fishes, with larger fish undergoing significantly less mortality. The role of dietary resources in the size-structuring process has not been well validated, especially at the early post-settlement phase, where competition and predation are seen as preeminent drivers of juvenile fish assemblage structure. Here, we report on a size differential of 10–20% between recently settled Siganus spinus rabbitfish recruits from different bays around the Pacific island of Guam. This difference was maintained across multiple recruitment events within and between years. After confirming the validity of our observations through otolith increment analysis, subsequent investigation into the drivers of this variation revealed significant differences in the structure of algal assemblages between bays, congruent with the observed differences in size of the recently settled fish. Gut analyses showed a greater presence of algal types with higher levels of nitrogen and phosphorus in the stomachs of fish from Tanguisson, the bay with the largest observed recruits. To ensure this mechanism was one of causation and not correlation, we conducted a fully factorial experiment in which S. spinus recruits sampled from different bays were reared on all combinations of algal diets representative of the different bays. Recruits on the ‘Tanguisson’ diet grew faster than recruits on other diets, regardless of their origin. We propose that the greater availability of high-quality dietary resources at this location is likely conferring benefits that impact on the population-level dynamics of this species. The spatial and temporal extent of this process clearly implicates food as a limiting resource, capable of mediating fish population dynamics at multiple spatial scales and ontogenetic phases.